2020
DOI: 10.1186/s40900-020-00189-3
|View full text |Cite
|
Sign up to set email alerts
|

“PROUD to have been involved”: an evaluation of participant and community involvement in the PROUD HIV prevention trial

Abstract: Background: The PROUD trial, a HIV prevention trial in men who have sex with men and trans women, set out to involve community representatives and trial participants in several ways. PROUD also aimed to evaluate participant involvement, to learn lessons and make recommendations for future clinical trials. Methods: Two structured surveys, one of participant and community representatives involved in the PROUD study, and the other of researchers from the PROUD team, were carried out in 2017. The results from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…While the PPI interactive evaluation form used for this study was sourced from an expert team on PPI research and referred previous studies [35][36][37] and PPI evaluation formats [38,39], its validity and reliability has not yet been confirmed. Globally, publications on the impacts of PPI on research quality have nearly tripled, increasing at an unprecedented rate [13,48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the PPI interactive evaluation form used for this study was sourced from an expert team on PPI research and referred previous studies [35][36][37] and PPI evaluation formats [38,39], its validity and reliability has not yet been confirmed. Globally, publications on the impacts of PPI on research quality have nearly tripled, increasing at an unprecedented rate [13,48].…”
Section: Discussionmentioning
confidence: 99%
“…The questionnaire used for the interactive evaluation was created by PPI experts of the team (KFujisawa and KM) based on previous studies [35][36][37] and PPI evaluation formats [38,39], which comprised 10 multiplechoice and two free-answer questions (Additional file 1: S1 and S2. Specific items of the multiple-choice portion of the interactive evaluation were tailored as appropriate, and a 3-5-point Likert scale was used for evaluation (Table 2).…”
Section: Standard Procedures For Ppi Meetingsmentioning
confidence: 99%
“…25 Such an approach, integrated in the UNAIDS/AVAC Good Participatory Practice guidelines, 26 has been successfully implemented in HIV preventive research and PrEP-related clinical trials and has been found to be beneficial to both researchers and PLWH involved. [27][28][29] Similar initiatives should be conducted for GMCT research.…”
Section: Discussionmentioning
confidence: 99%
“…We further excluded 25 studies for the following reasons: only conference abstract available (n = 11), study examines PPI on a theoretical level without providing guidance (n = 9), not about HIV (n = 2), not about HIV research only HIV service provision (n = 3). The remaining twelve studies were extracted in detail [17][18][19][20][21][22][23][24][25][26][27][28].…”
Section: Thementioning
confidence: 99%